2008
DOI: 10.3748/wjg.14.4257
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic fenestration of multiple giant biliary mucinous cystadenomas of the liver

Abstract: Biliary cystadenomas of the liver are rare, cystic neoplasms of the biliary ductal system usually occur in middle aged women. We report a case of synchronous multiple huge biliary mucinous cystadenomas with unique features. This is, according to our knowledge, the first report in the literature about three synchronously occurring hepatobiliary cystadenomas. Cystadenomas have a strong tendency to recur, particularly following incomplete excision, and a potential of malignant transformation. A therapeutic re-eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
(9 reference statements)
0
8
0
2
Order By: Relevance
“…The incidence of biliary cystadenomas is 1 in 20,000–100,000, while the risk of malignant transformation to adenocarcinoma has been reported to be as high as 20–23% 3. BMCAs are most commonly (85–95% of reported cases) seen in Caucasian females in middle age (55–65 years old) 4. The tumors are subcategorized into two subgroups: those that have mesenchymal tissue resembling ovarian stroma (OS) on histology and those that do not (nonOS).…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of biliary cystadenomas is 1 in 20,000–100,000, while the risk of malignant transformation to adenocarcinoma has been reported to be as high as 20–23% 3. BMCAs are most commonly (85–95% of reported cases) seen in Caucasian females in middle age (55–65 years old) 4. The tumors are subcategorized into two subgroups: those that have mesenchymal tissue resembling ovarian stroma (OS) on histology and those that do not (nonOS).…”
Section: Epidemiologymentioning
confidence: 99%
“…The tumors are subcategorized into two subgroups: those that have mesenchymal tissue resembling ovarian stroma (OS) on histology and those that do not (nonOS). While the former variant is much more common and seen exclusively in women, the latter has an equal distribution between men and women and is associated with an overall poorer prognosis and higher rate of recurrence 4,5. One study showed that women with OS variant BMCA were on average younger in age than their nonOS counterparts at the time of presentation/diagnosis and were generally within child-bearing age 6…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…(65) In fact, fenestration, aspiration, sclerosis, internal drainage, marsupialization or partial resection with or without cavity ablation can result in recurrence rate as high as 80-90%. (19, 70, 84, 85) As such, formal surgical resection with negative margins is recommended. (6-8) Appropriate surgical therapies may include liver resection or enucleation depending on the individual patient, anatomic position of the cyst, and surgeon experience.…”
Section: Managementmentioning
confidence: 99%
“…Furthermore, it presents the theoretical risk of tumour seeding, with one well-documented case of pleural carcinomatosis following percutaneous aspiration of a BCC [7]. Finally, intraoperative examination of frozen sections was not completely reliable in some series [4,23,24,25], in which it resulted negative for a BCC that was discovered afterwards on the formalin-fixed specimen. This is why final pathology report is needed before making any further prognostic judgement and therapeutic decision.…”
Section: Discussion Of the Indicationmentioning
confidence: 99%